Extrusion-based additive manufacturing of forming and molding tools - Strano, Matteo (Int J Adv Manuf Technol, 2021)
The production of rapid tools for plastic molding, sheet metal forming, and blanking has always been a critical and important goal for applied research, and a very large number of alternative methods have been proposed over the decades for their production. Among these methods, the use of extrusion-based additive manufacturing (EAM), such as fused filament fabrication (FFF) or similar technologies, has not been frequently considered and needs to be explored extensively. EAM is generally considered a low-cost, low-quality, low-performance class of AM and not suited to produce real functional parts, but only for aesthetical prototypes. However, the capabilities of EAM technologies have greatly evolved and now it is possible to extrude a wide range of materials such as polymeric materials including both the low strength polymeric materials (such as nylon or PLA) and the high strength polymeric materials (such as PEI and PEEK), metals (such as tool steel), and even ceramics (such as zirconia). Starting from an extensive literature review, the purpose of the present paper is to further demonstrate the potential applicability and versatility of EAM as a rapid tool manufacturing technology for different applications in shearing, bending, deep drawing, and injection molding.